Pemberdayaan Kader Pos Kesehatan Pesantren (POSKESTREN) dalam Penanganan Kegawatdaruratan di Pondok Pesantren Jabal Nur Kandis Kabupaten Siak Riau - Fajri Marindra Siregar; Riki Sukiandra (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Everyone including santri should have the ability to handle day-to-day emergencies. This community service activity aims to empower students who are cadres of Pesantren (Islamic Boarding House/Schools) health posts (Poskestren) in dealing with emergency cases. The community service was carried out by applying the Asset Based Community Development (ABCD) approach, by providing training to Poskestren cadres in the form of lectures and case simulations for handling situations and victims. Based on the results of the evaluation, it was found that there was an increase in the knowledge of the participants before and after participating in the activity, which means that the activity had a positive impact on the Pesantren students.